2007
DOI: 10.3102/0013189x07306523
|View full text |Cite
|
Sign up to set email alerts
|

High-Stakes Testing and Curricular Control: A Qualitative Metasynthesis

Abstract: Using the method of qualitative metasynthesis, this study analyzes 49 qualitative studies to interrogate how high-stakes testing affects curriculum, defined here as embodying content, knowledge form, and pedagogy. The findings from this study complicate the understanding of the relationship between high-stakes testing and classroom practice by identifying contradictory trends. The primary effect of high-stakes testing is that curricular content is narrowed to tested subjects, subject area knowledge is fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
561
3
54

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 852 publications
(699 citation statements)
references
References 50 publications
19
561
3
54
Order By: Relevance
“…Promotion of citizenship education occurs when people interact among groups for participatory communal citizenship during festivals or funerals in which members have the opportunity to teach local history and culture, and engage in multiple forms of civic learning. Several researchers (Au, 2007;Gee, 2013;Hoechsmann & Poyntz, 2012) have therefore recommended that teachers emphasize the use of media and technology to engage students in authentic citizenship learning experiences with others, construct knowledge, and communicate effectively. In one study focused on prospective teachers' ability to foster critical multicultural citizenship (Castro, 2010), findings showed that teaching strategies such as de-emphasizing the test, incorporating multicultural and critical content, and teaching multiple perspectives helped promote critical citizenship education.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Promotion of citizenship education occurs when people interact among groups for participatory communal citizenship during festivals or funerals in which members have the opportunity to teach local history and culture, and engage in multiple forms of civic learning. Several researchers (Au, 2007;Gee, 2013;Hoechsmann & Poyntz, 2012) have therefore recommended that teachers emphasize the use of media and technology to engage students in authentic citizenship learning experiences with others, construct knowledge, and communicate effectively. In one study focused on prospective teachers' ability to foster critical multicultural citizenship (Castro, 2010), findings showed that teaching strategies such as de-emphasizing the test, incorporating multicultural and critical content, and teaching multiple perspectives helped promote critical citizenship education.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In his meta-synthesis of scholarship on this topic, Au (2007) found that standardized, high stakes tests fragmented the "structure of knowledge" and increased "teacher-centered pedagogy" (p. 263). For example, the high stakes associated with the tests have often made teachers feel pressured to teach to the middle at the "expense of the lowest performing students" (Kesler, 2013, p. 510).…”
Section: Consequences Of High-stakes Examsmentioning
confidence: 99%
“…Uma consequência destas políticas é o estreitamento do currículo escolar (Au, 2007(Au, , 2009. Quando os testes incluem determinadas disciplinas e deixam outras de fora, os professores tendem a ensinar aquelas disciplinas abordadas nos testes (Madaus, Russell, & Higgins, 2009).…”
Section: Estreitamento Curricularunclassified